2021
DOI: 10.1016/j.cub.2021.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-dependent control of cytoskeleton and cell shape regulates division orientation in the Arabidopsis embryo

Abstract: Auxin-dependent control of cytoskeleton and cell shape regulates division orientation in the Arabidopsis embryo Graphical abstract Highlights d Auxin responses regulate directional cell expansion in Arabidopsis embryos d Cell shape and division orientation are tightly coupled d Transcriptome analysis identifies MT-associated IQD proteins in division control d Cytoskeletal dynamics control division orientation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Orientations can be computed with respect to the axes of a local coordinate system defined for the organ, along with its associated positional information ( Figure 8E and I , Figure 8—figure supplement 1A ). It is also possible to quantify how close cell divisions are to common division rules proposed in the literature, such as the shortest wall through the center of the cell including local minima ( Figure 8H ; Besson and Dumais, 2011 ; Yoshida et al, 2014 ; Vaddepalli et al, 2021 ) along the PDG ( Hejnowicz, 2014 )⁠, or rules based on network measures ( Jackson et al, 2019 )⁠.…”
Section: Resultsmentioning
confidence: 99%
“…Orientations can be computed with respect to the axes of a local coordinate system defined for the organ, along with its associated positional information ( Figure 8E and I , Figure 8—figure supplement 1A ). It is also possible to quantify how close cell divisions are to common division rules proposed in the literature, such as the shortest wall through the center of the cell including local minima ( Figure 8H ; Besson and Dumais, 2011 ; Yoshida et al, 2014 ; Vaddepalli et al, 2021 ) along the PDG ( Hejnowicz, 2014 )⁠, or rules based on network measures ( Jackson et al, 2019 )⁠.…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Plant Science 07 frontiersin.org Luptovčiak et al, 2017;Ovečka et al, 2020). Little is known about the molecular mechanism underlying this process, but recent studies suggested that auxin is deeply involved in determining cell division patterning (Yamaguchi et al, 2013;Marhavý et al, 2016;Huang et al, 2019;Vaddepalli et al, 2021). Huang et al (2019) demonstrated that auxin signaling regulates cell division patterning during lateral root development (Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An intermediate situation was observed in the inner apical domain, where the rule accounted for all but the longitudinal radial orientation. Auxin signaling has been suggested as required for cells to escape the default regime of division plane minimization and to control periclinal divisions at the previous (8C-16C) generation of cell divisions (Yoshida et al, 2014), which could involve a modulation of cell geometry by auxin signaling (Vaddepalli et al, 2021). At subsequent generations, it has instead been reported that the first vascular and ground tissue cells divided periclinally along their maximal (longitudinal) extension when the auxin response was impaired by a ARF5/MP mutation or local ARF inhibition (Möller et al, 2017).…”
Section: Discussionmentioning
confidence: 99%